Development of Natural and Social Science (IPAS) E-Modules Based on Project Based Learning to Improve The Collaboration Ability of Elementary School Students - Riyanto, Dwi Mahmud Rizki; Kawuryan, Sekar Purbarini (LPPM Universitas Pendidikan Mandalika, 2025)
This research aims to develop E-Modules of Natural and Social Sciences (IPAS) based on project-based learning to improve the collaboration skills of grade IV elementary school students that are feasible, practical, and effective. This research used a Research and Development (R&D) method with the ADDIE development model, which consists of five main stages: analysis, design, development, implementation, and evaluation. The subjects of this research were teachers and fourth-grade students in all primary schools in Tirtoadi, Mlati, Sleman, Yogyakarta. Observations, interviews, and questionnaires were used to collect data. The data analysis was qualitative and quantitative with an n-gain score test, independent t-test, and paired sample t-test. The results of research and development were in the form of IPAS e-module products based on project-based learning that are feasible, practical, and effective. The feasibility of the product from material experts and media experts obtained a percentage score of 88,71% with a very feasible category. The practicality of the product from the responses of educators and students obtained a percentage score of 81.58% with a very practical category. The effectiveness test results in an independent sample t-test showed a Sig. 0.022 < 0.05, and the paired sample t-test shows a Sig. 0.000 < 0.05. The results showed that the product was declared effective in improving the collaboration ability of grade IV elementary school students.